Impact of a Novel Two-Phase Natural Deep Eutectic Solvent-Assisted Extraction on the Structural, Functional, and Flavor Properties of Hemp Protein Isolates - Yi Chen; Wellington S. Oliveira; Fernanda F. G. Dias; Baraem P. Ismail (Plants)
Defatting dehulled hemp seeds is a crucial step prior to protein extraction. However, conventional methods rely on flammable solvents, posing significant health, safety, and environmental concerns. Additionally, hemp protein has poor extractability, challenging functionality, and flavor limitations, restricting its broader application in foods. Accordingly, a two-phase natural deep eutectic solvent (NADES)-assisted extraction was evaluated as a solvent-free alternative for co-extracting protein and oil from full-fat hemp flour. In comparison to the reference hemp protein isolate (R-HPI), produced from hexane-defatted flour following conventional alkaline extraction, NADES-extracted hemp protein isolate (N-HPI) had significantly higher protein extraction yield and purity. N-HPI exhibited enhanced surface charge, lower hydrophobicity, and thus higher solubility at an acidic pH compared to R-HPI. N-HPI had a higher abundance of edestin and lower levels of vicilin-like proteins, which contributed to superior gelation compared to R-HPI. N-HPI, compared to R-HPI, contained lower levels of lipid-derived off-flavor compounds, such as aldehydes, alcohols, and ketones. These findings highlighted, for the first time, the potential of a two-phase NADES-assisted extraction as a sustainable alternate and effective process for producing high-quality, functional hemp protein. The development of such a green process is an impetus for broadening the applications of hemp protein in food systems.